Policy entrepreneurs in times of uncertainty: How the idea of userdriven personal assistance came to fruition in Iceland - Sigurgeirsdóttir, Sigurbjörg (Stjórnsýslustofnun, 2016)
This research seeks to explain a landmark change in the provision of public services for people with disabilities in Iceland. Public policy has for long been characterized by incremental changes. Every now and then, major policy changes take place and longstanding policy objectives pushed by interest groups come through. Agenda-setting theories seek to explain major policy changes by focusing on how and why a policy issue gets on governments ? agenda at a given point in time. The American political scientist, John W. Kingdon, presented his theory of three streams and the window of opportunity some 30 years ago. European scientists maintain in their recent research that Kingdon ?s approach is helpful in shedding light on how the political system in which public policy-making takes place operates and how behaviour and strategies of those participating in the process influence the outcome. This qualitative research examines how the idea about user-driven personal assistance came to fruition in Iceland. The study is based on existing data and interviews with key people involved in the policy development leading to the decision to implement the programme of user-driven personal assistance. The research describes how and why this idea reached the government agenda and came to be implemented by Icelandic authorities. The conclusions show how the process of decentralisation opened opportunities for a new ideology which benefitted service users, and business as well as political interests. The conclusions indicate that not only was there a right man at the right place at the right time, but it provides theoretical explanations about what characterises policy entrepreneurs and how and why their activities matter in times of uncertainty. Þessi rannsókn leitast við að útskýra tímamótaákvörðun í þjónustu við fatlað fólk á Íslandi. Opinber stefnumótun hefur löngum einkennst af hægfara breytingum, sem gerast í smáum skrefum. Stundum bregður þó svo við að meiriháttar breytingar verða og stefnumál, sem verið hefur baráttumál ...